2021
DOI: 10.1530/eje-20-0767
|View full text |Cite
|
Sign up to set email alerts
|

Pegvisomant and Pasireotide LAR as second line therapy in acromegaly: clinical effectiveness and predictors of response

Abstract: Background: The treatment of acromegaly resistant to first generation somatostatin receptor ligands (SRLs) is often difficult. Pegvisomant and Pasireotide LAR are mostly used in these subset of patients, as second line therapies. Choice of the type of second line therapies is difficult, since predictors of response are still unclear, impairing personalized therapy. We aimed to investigate predictors of response to Pegvisomant and Pasireotide LAR. Methods: Seventy-four acromegaly patients entered this observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Reasons for the decrease of PEGV in combination with SRL/DA over time are likely multifactorial and varied due to treatment practices across countries and centres, but could be due to toleration issues, patient preference, cost of the combination therapy, radiation, and optimization of biochemical control. Use of combination treatment in acromegaly patients may benefit patients with aggressive acromegaly ( 6 ), particularly those partially resistant to first-generation SRLs and with large/invasive tumours ( 41 ), similar to those treated with PEGV and pasireotide ( 42 , 43 ). A recent study showed that low-dose SRL plus weekly PEGV represents a potential novel dosing option for achieving cost-effective, optimal biochemical control in patients with uncontrolled acromegaly requiring combination therapy ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the decrease of PEGV in combination with SRL/DA over time are likely multifactorial and varied due to treatment practices across countries and centres, but could be due to toleration issues, patient preference, cost of the combination therapy, radiation, and optimization of biochemical control. Use of combination treatment in acromegaly patients may benefit patients with aggressive acromegaly ( 6 ), particularly those partially resistant to first-generation SRLs and with large/invasive tumours ( 41 ), similar to those treated with PEGV and pasireotide ( 42 , 43 ). A recent study showed that low-dose SRL plus weekly PEGV represents a potential novel dosing option for achieving cost-effective, optimal biochemical control in patients with uncontrolled acromegaly requiring combination therapy ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that the higher dose of PAS-LAR needed to control a more biochemically active disease may have contributed to a greater glucose metabolism alteration. In fact, it is already known that in the presence of a more active disease at baseline, it is more difficult to obtain biochemical control of acromegaly [39]. Moreover, PAS-LAR has been shown to decrease insulin secretion acting at pancreatic beta cell level and to also decrease GlP and GLP-1 secretion [24].…”
Section: Discussionmentioning
confidence: 99%
“…Pasireotide shows the highest affinity for SST5, followed by SST2, SST3, and SST1 ( 79 ), although it has a slightly lower affinity -but still important- to SST2 than first-generation SRLs. In recent studies ( 15 , 80 , 81 ), it has been shown that in somatotropinomas depicting a SST5 immunohistochemical score of 2 or 3, a positive response to pasireotide is observed in about 50% of the cases resistant to first-generation SRLs; SST3 and AIP expression did not influence the response to pasireotide, while sparsely granulated adenomas responded better compared to densely granulated. However, in most of the tumors of unselected patients, pasireotide seems to exert its biological effects predominantly through SST2 ( 82 ).…”
Section: Molecular Markers Of Response To Pasireotidementioning
confidence: 97%
“…Besides the different receptor binding affinity, pasireotide exhibits different functional properties compared to first-generation SRLs when binding to SST5, and particularly SST2. However, in one of the recently published studies, high expression of SST5 was controversially associated with pasireotide resistance in some cases ( 81 ). Also, AIP low expression tumors may be pasireotide-responsive, indicating that this pathway is not exclusively implicated in the biological response to pasireotide, in opposition to what happens with first-generation SRLs, in which it plays an important role; this has been recently described in AIP mutated acromegaly patients ( 84 ).…”
Section: Molecular Markers Of Response To Pasireotidementioning
confidence: 99%
See 1 more Smart Citation